Multi-Species fluxes for the parallel quiet direct simulation (QDS) method - Cave H.M.; Lim C.-W.; Jermy M.C.; Krumdieck S.P.; Smith M.R.; Lin Y.-J.; Wu J.-S. (2023)
Fluxes of multiple species are implemented in the Quiet Direct Simulation (QDS) scheme for gas flows. Each molecular species streams independently. All species are brought to local equilibrium at the end of each time step. The multi species scheme is compared to DSMC simulation, on a test case of a Mach 20 flow of a xenon/helium mixture over a forward facing step. Depletion of the heavier species in the bow shock and the near-wall layer are seen. The multi-species QDS code is then used to model the flow in a pulsed-pressure chemical vapour deposition reactor set up for carbon film deposition. The injected gas is a mixture of methane and hydrogen. The temporal development of the spatial distribution of methane over the substrate is tracked. 2011 American Institute of Physics.